A STUDY OF ILLOCUTIONARY SPEECH IN TRADITIONAL MARKETS IN PRAGMATIC PERSPECTIVE - Muhammad Riyanton; Mustasyfa Thabib Kariadi; Umi Ana Setiana (Jurnal Ilmiah Teunuleh, 2020)
Abstract The interaction conducted by traders with buyers in Kejajar Wonosobo Market intends to reach a final agreement in transaction activities. In the final agreement, there is an interesting thing that needs to be observed, namely the use of certain words that have the influence of the seller on the buyer. The power of influence is a speech that can be understood by speakers and speech partners. The power of influence is known as the act of speech illocution. In this article, the author aims to describe the type and function of illocution speech and its relevance to Indonesian language learning in high school. Based on the results of data analysis found 41 speech data included in the type and function of illocution speech actions carried out by sellers with buyers in Kejajar Wonosobo Market. The data included 7 data on expressive speech types, 17 data on the type of corrective speech directive, 11 data on the type of corrective speech, and 6 data types of commission speech, while the type of declarative illocution speech was not found. In addition, the illocution speech function was found to consist of 17 competitive function data, 13 convivial function data, 11 collaborative function data, while for conflictive illocution speech function was not found. Furthermore, the results of this study were integrated into Indonesian language learning in negotiation text material in high school grade X, in KD 3.11: Analyzing the content, structure (orientation, submission, offer, approval, closing) and language of the negotiating text.